2015
DOI: 10.5603/ait.2015.0048
|View full text |Cite
|
Sign up to set email alerts
|

Nieinwazyjna ocena układu krążenia przy użyciu urządzenia Nexfin pozwala na ocenę ryzyka wystąpienia hipotensji spowodowanej znieczuleniem podpajęczynówkowym

Abstract: Background: Unfavourable circulatory system conditions have been observed in many patients with spinal anaesthesia. The most frequent symptoms include a decrease in blood pressure and, less frequently, bradycardia. The appearance of unfavourable consequences of spinal anaesthesia might be related to the initial status of the patient's circulatory system. The aim of this study was to establish the possibility of predicting unfavourable circulatory consequences (hypotension, bradycardia) following spinal anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We measured electrocardiography (ECG), heart rate (HR; beats min), blood saturation (SpO 2 : percentages), non-invasive blood pressure (NIBP; mm Hg), sedation level on the Richmond Agitation and Sedation Scale (RASS), pain intensity level on the Visual Analogue Scale (VAS) and the Prince Henry Hospital Pain Score (PHHPS). Similarly to Ławicka et al [11], in measuring haemodynamic parameters using the non-invasive method, the ClearSight device was used to measure CO, CI, SVI, SVV, SVI and SVRI [11]. Data were recorded every hour.…”
Section: Methodsmentioning
confidence: 99%
“…We measured electrocardiography (ECG), heart rate (HR; beats min), blood saturation (SpO 2 : percentages), non-invasive blood pressure (NIBP; mm Hg), sedation level on the Richmond Agitation and Sedation Scale (RASS), pain intensity level on the Visual Analogue Scale (VAS) and the Prince Henry Hospital Pain Score (PHHPS). Similarly to Ławicka et al [11], in measuring haemodynamic parameters using the non-invasive method, the ClearSight device was used to measure CO, CI, SVI, SVV, SVI and SVRI [11]. Data were recorded every hour.…”
Section: Methodsmentioning
confidence: 99%
“…The overall incidence of hypotension was low, which could be attributed to a relatively low block and compensatory mechanisms in young subjects. In a recent study Lawicka et al (52) showed that in patients aged around 40-years of age ASA status 1 and 2, the incidence of hypotension with the spinal block around 6th thoracic segment was 39%. The incidence of hypotension was similar to our group H in which spinal block level was around Th4, although a much lower dose of hyperbaric bupivacaine was used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension is a common hemodynamic side effect after spinal anesthesia (SA), which may lead to increased morbidity and mortality [1] . Since spinal anesthesia is easy to apply, it is preferred in lower abdominal, inguinal, urogenital, rectal, and lower extremity surgeries.…”
Section: Introductionmentioning
confidence: 99%